Cervicovagopathy: ligamentous cervical instability and dysstructure as a potential etiology for vagus nerve dysfunction in the cause of human symptoms and diseases - Ross A. Hauser; Danielle Matias; Benjamin Ryan Rawlings (Frontiers in Neurology)
Vagus nerve dysfunction is implicated in the pathophysiology of many different symptoms and diseases that plague humanity. In many cases, the etiology of this condition remains elusive. One potentially implicating factor is cervical spine pathology, as the 2 vagus nerves are located in the carotid sheath just anterior to the cervical vertebrae. We propose that cervicovagopathy occurs primarily by the slow stretching of the posterior cervical ligaments because of a forward head-facedown lifestyle from excessive cell phone and computer usage. While the excessive stretch and compression on the vagus nerve initially just inhibits electrical impulses (conduction block), the condition progresses to ligamentous cervical instability. It ultimately results in a breakdown of the cervical curve (dysstructure), leading to vagus neuron cell death (degeneration), which can be documented by carotid sheath ultrasound. Cervical structural, internal jugular vein, and vagus nerve cross-sectional area measurements are presented from a retrospective chart review of 234 consecutive patients with no obvious cause for 1 of 9 specific symptoms—anxiety, dizziness, fatigue, irritability, lightheadedness, insomnia, sleeping difficulty, neck pain, and neck cracking/popping. Those cases of vagus nerve degeneration from a structural cause require corrective cervical structural therapies such as proper ergonomics, physiotherapy, cervical curve and postural exercises, low-force adjustments, and prolotherapy. A case example is given to demonstrate how cervical structural treatments can open up internal jugular veins and improve a patient’s chronic symptoms. Resolution of symptoms that occur alongside improvements in vagus nerve cross-sectional areas (regeneration), correlating with restoration of the cervical lordotic curve and stability, will prove this hypothesis.